Cost Effective Solution for a Shunt Hybrid Filter Using Enhanced Current Controller - Y. Lalitha Kameswari; O. Chandra Sekhar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The increasing demand of energy and development of distributed generation systems have led to great progress in medium voltage high-power inverters. On the other side, due to more intransigent regulations in the area of power quality and appearance of new grid codes, which limit the harmonics’ amounts in ac grids, special attention has to be made to restrict the harmonics. The recently proposed selective harmonic mitigation pulse width modulation method reduces the values of specific harmonics to meet the grid codes, instead of making them zero. In this way, there are much more solutions for mitigating the same harmonics which in the Selective Harmonic Eliminated Pulse-Width Modulation (SHEPWM), are completely eliminated. The SHMPWM was first introduced in, where a waveform  having 750 Hz switching frequency was employed to mitigate harmonics up to 49th to satisfy the grid codes EN 50160 and CIGRE WG 36-05 without using any filtering system. In this contribution a solution to the parallel resonance problem that can be present in practical applications of shunt Active Power Filter (APF) compensation is proposed. The proposed solution involves turning the shunt APF scheme of compensation into a Shunt Hybrid Filter (SHF) configuration. A Linear Quadratic Regulator (LQR)-based switching controller was specifically designed for this hybrid scheme of compensation, maintaining stringent performance requirements on the tracking of filtering currents and the draining of the harmonic ripple currents.